Short and long-lasting behavioral consequences of agonistic encounters between male Drosophila melanogaster - Trannoy, Séverine (Proc Natl Acad Sci U S A, 2016)
In many animal species, learning and memory have been found to play important roles in regulating intra- and interspecific behavioral interactions in varying environments. In such contexts, aggression is commonly used to obtain desired resources. Previous defeats or victories during aggressive interactions have been shown to influence the outcome of later contests, revealing loser and winner effects. In this study, we asked whether short- and/or long-term behavioral consequences accompany victories and defeats in dyadic pairings between male Drosophila melanogaster and how long those effects remain. The results demonstrated that single fights induced important behavioral changes in both combatants and resulted in the formation of short-term loser and winner effects. These decayed over several hours, with the duration depending on the level of familiarity of the opponents. Repeated defeats induced a long-lasting loser effect that was dependent on de novo protein synthesis, whereas repeated victories had no long-term behavioral consequences. This suggests that separate mechanisms govern the formation of loser and winner effects. These studies aim to lay a foundation for future investigations exploring the molecular mechanisms and circuitry underlying the nervous system changes induced by winning and losing bouts during agonistic encounters.